Tunable 2D Group‐III Metal Alloys. Issue 44 (4th September 2021) - Rajabpour, Siavash; Vera, Alexander; He, Wen; Katz, Benjamin N.; Koch, Roland J.; Lassaunière, Margaux; Chen, Xuegang; Li, Cequn; Nisi, Katharina; El‐Sherif, Hesham; Wetherington, Maxwell T.; Dong, Chengye; et al.
Abstract: Chemically stable quantum‐confined 2D metals are of interest in next‐generation nanoscale quantum devices. Bottom‐up design and synthesis of such metals could enable the creation of materials with tailored, on‐demand, electronic and optical properties for applications that utilize tunable plasmonic coupling, optical nonlinearity, epsilon‐near‐zero behavior, or wavelength‐specific light trapping. In this work, it is demonstrated that the electronic, superconducting, and optical properties of air‐stable 2D metals can be controllably tuned by the formation of alloys. Environmentally robust large‐area 2D‐In x Ga1− x alloys are synthesized byConfinement Heteroepitaxy (CHet). Near‐complete solid solubility is achieved with no evidence of phase segregation, and the composition is tunable over the full range of x by changing the relative elemental composition of the precursor. The optical and electronic properties directly correlate with alloy composition, wherein the dielectric function, band structure, superconductivity, and charge transfer from the metal to graphene are all controlled by the indium/gallium ratio in the 2D metal layer. Abstract : Air‐stable large‐area 2D‐In x Ga 1−x alloys with tunable composition and no evidence of phase segregation are realized by confinement heteroepitaxy. The optical and electronic properties directly correlate with alloy composition, wherein the dielectric function, band structure, superconductivity, and charge transfer from the metal to graphene are all controlled by the indium/gallium ratio in the 2D metal layer.